1965
DOI: 10.1136/jnnp.28.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion of the vertebral artery

Abstract: The angiographic demonstration of an occluded vertebral artery in a patient with a brain-stem syndrome was first reported by Riechert in 1952, and similar cases have been described by various authors subsequently. The common site of the vertebral occlusion was in the area between the arch of the atlas and the junction of the vertebral arteries. Since routine brachial angiography has been initiated in this clinic, occlusion of the vertebral artery at this site has been noticed more frequently than expected. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

1969
1969
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Vertebral artery occlusion (VAO) was first described by Riechert in 1952 in angiography of a patient with a brain-stem syndrome; later, similar cases were reported. 1 VAO is a potentially life-threatening scenario and may cause serious and even fatal neurological deficits due to brain-stem and cerebellar infarctions. This may result in stroke or may give rise to isolated or combined symptoms and signs of altered consciousness, speech defects, diplopia, blurred vision, nystagmus and dysphagia.…”
Section: Introductionmentioning
confidence: 99%
“…Vertebral artery occlusion (VAO) was first described by Riechert in 1952 in angiography of a patient with a brain-stem syndrome; later, similar cases were reported. 1 VAO is a potentially life-threatening scenario and may cause serious and even fatal neurological deficits due to brain-stem and cerebellar infarctions. This may result in stroke or may give rise to isolated or combined symptoms and signs of altered consciousness, speech defects, diplopia, blurred vision, nystagmus and dysphagia.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the important clinico-pathological case histories described by F isher el al. [1961] and by Y ates and H utchinson [1961], and the surgical cases of de Backey et al [1962], we have found only isolate case reports, [2,11,12,21,22,25,28],In the present paper we describe two patients who were observed re cently, in Psychiatric Hospital of Reggio Emilia, and in Psychiatric Institut 'Paolo Pini' of Milan. …”
mentioning
confidence: 85%
“…These general principles are illustrated by many instances where com plete occlusion of both vertebral arteries [1,14,26,28] has not led to any obvious clinical consequence; in such subjects the circle of Willis has been fully patent and has immediately permitted the carotid circulation to draw blood from the vertebral circulation, or vice-versa. In one patient of ours, reported in an earlier paper [19b], it was demonstrated beyond doubt that not a single abnormality, clinical sign or symptom, could be detected in a subject whose brain was being supplied solely by the left vertebral artery, but where the circle of Willis was evidently perfectly effective.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A polycytaemia vera myeloproliferativ betegség, mely a fokozott vérviszkozitás miatt szintén hozzájárulhat thromboemboliás folyamatok kialakulásához [9]. Az a. vertebralis elzáródásának leggyakoribb helye az atlas ívének és az a. vertebralisnak a találkozása közötti terület [10].…”
Section: Esetismertetésunclassified